Effects of Graded Doses of Nitrogen , Phosphorus and Potassium on the Growth and Leaf Nutrient Status in Cocoa - Salikutty Joseph (Department of Plantation Crops and Spices, College of Horticulture, 1981)
Investigations were carried out at the College of Horticulture , Vellanikkara during 1979-80 to study the effect of graded doses of nitrogen , phosphorus and potassium on the growth and leaf nutrient status of cocoa . The results of a pot culture experiment in completely Randomised Design revealed that growth parameters (height, girth and number of leaves) as well as dry matter production remained unaffected following the application of nitrogen , phosphorus and potassium. The studies indicated that addition of fertilisers to seedling grown in potmixture may not be necessary . It has also been observed that the uptake of nitrogen , phosphorus and potassium by cocoa seedlings was not affected by varying levels of these nutrients. Leaf ranked fifth from the apwas found to be suitable for leaf analysis in cocoa seedlings. Field grown young cocoa trees were utilised for evaluating the relationships between soil test values and leaf nutrient concentration vis a vis plant growth.The studies indicated the suitability of either fan or chupon leaves for foliar nutrient analysis in cocoa. However, indiscriminate sampling between the two types is to be avoided . No significant correlations existed between phosphorus and potassium contents in soil leaf, and tree growth.